A self-assembled Cu( ii ) 4 [2 × 2] grid with organic radicals - Shuvaev, Konstantin V.; Sproules, Stephen; Rautiainen, J. Mikko; McInnes, Eric J. L.; Collison, David; Anson, Christopher E.; Powell, Annie K. (Dalton transactions : an international journal of inorganic chemistry, 2013)
A novel multitopic, two-pocket ligand HL(nit), containing the nitronyl nitroxide radical, has been designed for a self-assembled [2 × 2] grid system. HL(nit) is not stable in methanol and slowly undergoes a disproportionation, during which the nitronyl nitroxide radical converts to the diamagnetic amidino oxide. In situ reaction of HL(nit) with Cu(BF(4))(2) in methanol depending on the reaction time affords self-assembled [2 × 2] grids (L(nit))(2)(L)(2)Cu(II)(4)(BF(4))(4)·CH(3)OH (1) or (L(nit))(0.5)(L)(3.5)Cu(II)(4)(BF(4))(4)·CH(3)OH (2), in which L contains an amidino oxide arising from a 3-electron reduction of the nitronyl nitroxide radical. The percentages of stable radical in grids 1 and 2 as determined by X-ray are 50 and 12.5%, respectively. Structures 1 and 2 contain a six-coordinated distorted Cu(II) that is oxo-bridged at 140°. The nitronyl nitroxide radical coordinates via the oxo-atom of the N(+)-O(-) fragment in a chelating fashion and lies in the equatorial plane of the metal ion. The magnetic properties of 1 could be fitted to a 5-spin Hamiltonian with J(Cu-Cu) = +3.1 cm(-1) and J(Cu-Nit) = -278 cm(-1), while those of 2 to a 4-spin Hamiltonian with J(Cu-Cu) = +2.9 cm(-1). The Q-band EPR spectra of 1 and 2 recorded in solution at 20 K showed intricate anisotropic features of the Cu(II) ion and a much weaker signal of the -NO˙ fragment, associated with a strong Cu(II)-Nit antiferromagentic coupling. The DFT calculated (B3LYP/TZVP/6-31G*) magnetic coupling constants for the grid of 1 were J(Cu-Cu) = +5 cm(-1) and J(Cu-Nit) = -282 cm(-1), which are in very good agreement with the experimentally obtained values.